Kaonic atoms at the DAΦNE collider with the SIDDHARTA-2 experiment. (1st August 2022) - Napolitano, F; Sgaramella, F; Bazzi, M; Bosnar, D; Bragadireanu, M; Carminati, M; Cargnelli, M; Clozza, A; Deda, G; De Paolis, L; Del Grande, R; Fabbietti, L; et al.
Abstract: Kaonic atoms are a unique tool to explore quantum chromodynamics in the strangeness sector at low energy, with implications reaching neutron stars and dark matter. Precision x-ray spectroscopy can fully unlock the at-threshold isospin dependent antikaon-nucleon scattering lengths, via the atomic transitions to the fundamental level. While the SIDDHARTA experiment at the INFN-LNF DAΦNE collider successfully measured kaonic hydrogen, its successor SIDDHARTA-2 is starting now its data taking campaign aiming to finally fully disentangle the isoscalar and isovector scattering lengths via the measurement of kaonic deuterium. An overview of the first experimental results from a preparatory run for the SIDDAHARTA-2 experiment is presented.